2017
DOI: 10.5114/ada.2017.67845
|View full text |Cite
|
Sign up to set email alerts
|

CD207+/langerin positive dendritic cells in invasive and in situ cutaneous malignant melanoma

Abstract: A b s t r a c tIntroduction: Dendritic cells are crucial for cutaneous immune response. Their role in melanoma progression is however a matter of controversy. Material and methods: The number of dendritic cells within epidermis and in peri-and intratumoral location was analyzed using CD207 immunostain in 17 cases of in situ and 25 case of invasive melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Immature LCs are potent inducers of immune tolerance; however, upon maturation these cells are capable of activating effective antigen-specific immune responses ( 132 ). Infiltration of immature CD207 + /Langerin + DCs in the peritumoral area of invasive cutaneous malignant melanoma (CMM) is correlated with increased tumor growth, a high mitotic rate, and CMM ulcer development, all leading to disease exacerbation and a worse prognosis ( 133 ). Also, the infiltration of Langerin + cells in Hodgkin lymphomas and in nasopharyngeal carcinomas has been associated with the already well-characterized, strong immunosuppressive tumor microenvironment in these two types of cancers ( 134 ).…”
Section: Interaction With the Immune Systemmentioning
confidence: 99%
“…Immature LCs are potent inducers of immune tolerance; however, upon maturation these cells are capable of activating effective antigen-specific immune responses ( 132 ). Infiltration of immature CD207 + /Langerin + DCs in the peritumoral area of invasive cutaneous malignant melanoma (CMM) is correlated with increased tumor growth, a high mitotic rate, and CMM ulcer development, all leading to disease exacerbation and a worse prognosis ( 133 ). Also, the infiltration of Langerin + cells in Hodgkin lymphomas and in nasopharyngeal carcinomas has been associated with the already well-characterized, strong immunosuppressive tumor microenvironment in these two types of cancers ( 134 ).…”
Section: Interaction With the Immune Systemmentioning
confidence: 99%
“…These mechanisms are probably responsible for the association of worse prognosis in different neoplasms with high degree infiltration with DCs, and especially CD123-and CD207-positive cells. These correlations are observed in melanoma, when the infiltration is higher in different parts of the tumour [28,29]. The infiltration with CD123-positive cells as bad predictor is also described in breast cancer, where the high degree of infiltration is an in dependent prognostic factor for determining survival and prognosis [30,31].…”
Section: Discussionmentioning
confidence: 83%
“…83 Post-hoc analysis of the Sunbelt trial results regarding the impact of ulceration of the primary tumor on adjuvant IFNtreatment efficacy in sentinel node positive patients demonstrated that a significant improvement of disease-free survival was observed only in IFN-treated patients with an ulcerated primary. 78,84 While IFN therapy use in melanoma has declined since the completion of these trials, the results indicate a clear difference in the tumor immune response when ulceration is present in the primary tumor. The impact of ulceration should therefore be considered in the evaluation of any melanoma immune-based treatment.…”
Section: Interferonsmentioning
confidence: 99%
“…More immunosuppressed dendritic cells [77] ↑ peritumoral CD207/langerin+ dendritic cells [78] ↓ LAMP+ dendritic cells [77] Cytokine profile ↑ IL6 gene expression [12] Response to therapy ↑ response to adjuvant IFN [11,[80][81][82][83][84] Clinical, Cosmetic and Investigational Dermatology 2022:15 https://doi.org/10.2147/CCID.S372287…”
Section: Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation